Pengabdian Masyarakat Workshop Tripartit Kebijakan Super Tax Deduction Pemagangan Pendidikan Vokasional - Yuyun Estriyanto; Valiant Lukad Perdana Sutrisno; Taufik Wisnu Saputra; Indah Widiastuti; Suharno Suharno (DEDIKASI: Community Service Reports, 2021)
In 2019, the Ministry of Finance issued a Super Tax Deduction policy, a tax incentive provided by the government to businesses/industries involved in vocational education programs, including research and development activities to generate innovation. This program provides a maximum gross income reduction of up to 200% of the total costs incurred for work practices, apprenticeship, and/or vocational education learning services. This program is designed to encourage establishing a link-and-match between the world of education and industry to improve the quality of human resources produced by the education sector. Two years since its launch, the socialization of this program has not been optimal. Only a handful of industries have taken advantage of this program. Information that does not reach stakeholders causes the program not to run as expected. The tripartite workshop that brings together all stakeholders is expected to be able to share perceptions regarding the nature and technical implementation of the policy.